Creating Catholics : catechism and primary education in early modern France - Carter, Karen E., 1973- (UPCC book collections on Project MUSE., 2011)
The religious education of children represents a critical component of the Catholic Reformation that has often been overlooked by historians of early modern Europe. In Creating Catholics: Catechism and Primary Education in Early Modern France, Karen E. Carter examines rural schooling in France in the seventeenth and eighteenth centuries--the period when community-supported primary education began--and brings to light a significant element of the early modern period. Carter scrutinizes Catholic religious education in rural parishes in France through its two leading forms: the explosion of Catholic catechisms for children and their use in village schools. She concentrates on educational opportunities for rural peasants in three French dioceses: Auxerre (in Burgundy) and Chalons-sur-Marne and Reims (in Champagne). Carter argues that the study of catechism in village schools was an integral part of a comprehensive program, implemented by both clerical and lay leaders, for the religious, ethical, and moral education of children. Her research demonstrates that the clergy and a majority of the lay population believed in the efficacy of this program; for this reason, parish priests taught catechism in their parishes on a weekly basis, and small village communities established and paid for a surprisingly large number of local schools so that their sons and daughters could receive an education both in basic literacy skills and, through memorization of catechism, in Catholic faith and practice.